Aquisição da escrita alfabética em escolas democráticas implicações epistemológicas e educacionais - Sasso, Bruna Assem (Editora Oficina Universitária, 2022)
"The book Acquisition of alphabetic writing in democratic schools: epistemological and educational implications, by Bruna Assem Sasso, brings great contributions to teachers and students in the area of Education regarding the history of Piagetian ideas in Brazil, as well as the assimilation of Psychogenesis in the state of São Paulo in the 1980s. It also discusses the way in which two democratic schools, one private and the other public, appropriated the said Theory. The author writes in a clear and inviting way, holding the reader's attention." PROF. DR. MARIA LUCIA MARQUES.